Keeping safe and fed: large heterospecific shorebird flocks to decrease intraspecific competition - Cestari, Cesar; Goncalves, Cristina da Silva [UNESP]; Melo, Celine de (Wiley-Blackwell, 2020)
Shorebirds join cohesive flocks for safety. The joining of individuals of several species in large heterospecific flocks can optimise individual vigilance and foraging. However, a large number of conspecific individuals in flocks may deplete food resources and increase intraspecific competition. In the present study, we argue that Nearctic-Neotropical migratory shorebird species join large heterospecific flocks in a balanced number as a way of controlling intraspecific competition. We recorded monospecific and heterospecific flocks in urban beaches from southeastern Brazil and annotated the species richness and the number of individuals per bird species per flock. Besides, we recorded the number of people around shorebird flocks to examine any relationship with flock size. We also recorded the foraging rate of the semipalmated plover Charadrius semipalmatus, a common migrant species in the region, as a species model to test competition and vigilance. We hypothesised that this species would exhibit a low foraging rate in scenarios with high intraspecific competition (i.e. large flocks with a high number of conspecifics) and high density of people, which may disturb birds. In the initial results, the density of people did not influence size of monospecific and heterospecific flocks; heterospecific flocks were larger than monospecific flocks, and heterospecific flocks increased in size by the addition of more species rather than more individuals of the same species. These data reflect a decrease in the relative abundance of individuals per species. Additionally, the semipalmated plover foraging rate was reduced in monospecific flocks, flocks with a high relative abundance (and total number) of the specific individuals and flocks surrounded by a high density of people. All these results indicate that shorebirds may adjust flock composition and size according to preferred foraging conditions, i.e. large and balanced heterospecific flocks with less intraspecific competition and less vigilance to potential predators in wintering areas.
Keywords: behaviour; biodiversity; birds; coast; ecological niche; mixed-species